The Dynamics of Minimum Wages and Inflation: Implications for Employment Opportunities in the Manufacturing Sector - Asriati; Ismail Rasulong; Arfinayanti Syam (Pustaka Digital Indonesia, 2024)
This study aims to analyze the impact of minimum wages and inflation on employment opportunities in the manufacturing sector in Gowa Regency from 2014 to 2023. Using a quantitative approach and multiple linear regression analysis, this research examines the influence of minimum wages and inflation as independent variables on employment opportunities as the dependent variable. Secondary data were sourced from the Central Statistics Agency (BPS) and related institutions. The results reveal that minimum wages have a positive and significant effect on employment opportunities, supporting the efficiency wage theory, where wage increases drive higher labor productivity and employment absorption. Conversely, inflation does not significantly influence employment opportunities, indicating that other factors, such as investment and regional economic growth, may have a stronger impact. The findings highlight the importance of well-designed minimum wage policies in enhancing job opportunities, particularly when supported by improved workforce quality. Policymakers are advised to ensure that wage policies align with local economic conditions and are complemented by programs that enhance worker skills and productivity. Furthermore, addressing other determinants, such as investment and fiscal policies, is essential for fostering sustainable employment growth in the manufacturing sector. This study contributes to a deeper understanding of regional labor market dynamics and provides practical insights for local governments to drive economic development and create quality employment opportunities.